Health and Economy in COVID-19 Era: A Plan for Reconstituting Long-Term Economic Security - Allen, Mary Beth; Mirsaeidi, Mehdi (Frontiers in Public Health, 2020)
COVID-19 is a rapidly evolving pandemic which represents a multifaceted global threat. Given the economic consequences, most researchers agree that social distancing measures are an effective strategy relative to the cost. Previous studies indicate that community size as well as viral population risk groups should be considered in forming an effective targeted social distancing strategy. The resultant delay in the occurrence of infections in order to support vaccine development has been shown to be an effective policy. However, a return to normalcy from the current situation would require policy intervention that transforms the American economy along with continued targeted social distancing and the use of medical science as a tool to facilitate gradual personal interactions of low-risk individuals. We believe that the adoption of rapid IgG testing would be best suitable for widespread population-level screening as part of a comprehensive plan for incrementally rebuilding the in-person workforce. As such, this crisis represents an opportunity for the United States to increase automation of the manufacturing sector, shrink supply chains, and create higher-level jobs in order to reduce the dependency on other countries for critical supplies. This economic transition to better utilize technology along with reconstruction of the workforce could improve the standard of living for many Americans as well as better prepare the US for future pandemics.